Backscattered electron imaging of high pressure frozen soybean root nodules visualizes formation of symbiosome membranes. (12th December 2018) - Kaneko, Yasuko; Sharmin, Farhana; Bulbul, Nayeema; Atsuzawa, Kimie
Abstract : High-pressure frozen soybean root nodules were fractured to obtain backscattered electron images from uncoated samples in a low vacuum SEM equipped with a cryo-transfer system. Membrane accumulation near nuclei, and vesicles and tubular membranes, which possibly contribute to symbiosome membrane formation, were observed in a near native state. Abstract: High-pressure frozen soybean root nodules were fractured and backscattered electron images were obtained from uncoated samples in a low vacuum scanning electron microscope equipped with a cryo-transfer system. Structures of infected cells were well preserved: numerous symbiosomes, as well as nuclei, plastids and mitochondria were observed without ice crystal damage. After appropriate sublimation of water, bacteria included in symbiosomes were visualized. Membrane accumulation near nuclei, and vesicles and tubular membranes, which possibly contribute to symbiosome membrane formation, could be observed in a near native state. The method promises to be widely applicable to visualize interaction between membranes in various biological systems.